Efficacy of parathyroid autotransplantation in endoscopic total thyroidectomy with CLND - Cheng, Xiaozhou; Li, Yaping; Chen, Lijun (Frontiers in Endocrinology, 2023)
Purpose To evaluate the safety and efficacy of autologous parathyroid transplantation in laparoscopic total thyroidectomy combined with central lymph node dissection (CLND). Methods Retrospective analysis of clinical data of 152 patients admitted to the General Surgery Department of Gansu Provincial People’s Hospital who underwent endoscopic total thyroidectomy combined with CLND from June 2018 to December 2021. The intraoperative parathyroid glands were divided into the orthotopic preservation group (non-transplantation group) and the immediate active autologous transplantation group (transplantation group) according to the different treatment management of parathyroid glands during operation. The levels of Ca2+ in parathyroid blood and the incidence of hypoparathyroidism were compared between the two groups before operation and 1 day, 3 day, 1 week, 1 month, 3 months and 6 months after operation. Results There was no significant difference in PTH between the preoperative transplantation group compared and the non-transplantation group (P>0.05); The PTH in the transplantation group was lower than that of the non-transplantation group 1 and 3 d after surgery, and the difference was statistically significant (P<0.05); No statistically significant difference in PTH between patients in the transplantation group compared with those in the non-transplantation group at 1 week postoperatively (P>0.05); PTH was significantly higher in the transplant group than in the non-transplant group at 1, 3 and 6 months after surgery, with statistically significant differences (P<0.05); there was no statistically differences (P>0.05) in serum Ca2+ between the preoperative, 1d, 3d and 1 week postoperative transplantation group and the non-transplantation group; Blood Ca2+ was significantly higher in the transplant group than in the non-transplant group at 1, 3 and 6 months after surgery, with statistically significant differences (P<0.05); The rate of temporary hypoparathyroidism in the transplantion group was higher than that in the non-transplantion group, and the rate of permanent hypoparathyroidism was lower than that in the non-transplantion group (P=0.044); There was no significant difference in the concentration of PTH in the cephalic vein of the elbow between the transplanted side and the non-transplanted side at 1 day and 3 days postoperatively (P>0.05); the concentration of PTH in cephalic vein of the elbow was significantly higher than that in non-transplanted side at 1 week, 1 month, 3 months and 6 months postoperatively (P<0.001); the number central area dissection and metastasis dissection in the transplantation group were significantly higher than those in the non-transplantation group (P<0.05). Conclusions Most autologous parathyroid glands, having functional parathyroid autograft, is helpful to the occurrence of hypoparathyroidism after endoscopic total thyroidectomy with CLND, and it is an effective strategy to prevent permanent hypoparathyroidism, and more thorough area dissection is beneficial to the disease prognosis.